6.2=2.2+z

Simple and best practice solution for 6.2=2.2+z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6.2=2.2+z equation:


Simplifying
6.2 = 2.2 + z

Solving
6.2 = 2.2 + z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
6.2 + -1z = 2.2 + z + -1z

Combine like terms: z + -1z = 0
6.2 + -1z = 2.2 + 0
6.2 + -1z = 2.2

Add '-6.2' to each side of the equation.
6.2 + -6.2 + -1z = 2.2 + -6.2

Combine like terms: 6.2 + -6.2 = 0.0
0.0 + -1z = 2.2 + -6.2
-1z = 2.2 + -6.2

Combine like terms: 2.2 + -6.2 = -4
-1z = -4

Divide each side by '-1'.
z = 4

Simplifying
z = 4

See similar equations:

| 4-1/0-5 | | (3x+1)-4=4 | | 8.2=10x+7.7 | | -(x^10/32)^4/5 | | 4.4=z-5.6 | | 16x-3=12x+15 | | x-6=5x-24 | | 0.05(10000)+0.08x=0.068(10000+x) | | 5(w-2)=30 | | 4.25+4c=1.8 | | 40x+20=145 | | -6+2(x+3)=24-x | | 8x=3-6x | | -2x^2-7x=-1.5 | | 4c+26=62 | | 9x-1=9(x-6) | | 4x+8+6=3x+6 | | cot*2*x=-2.1 | | 8/tan70 | | Csquared-4c=0 | | 0=-2x^3+15x^2-24x+20 | | 27=103-2f | | y=-2x^3+15x^2-24x+20 | | -(5+4n)=9-6n | | -3(4x-4)+5=-12x+17 | | 2.33+3n=0.8n+15 | | 2-5x=2x-26 | | 6+5x+1-3x=-3+4x+4-3x | | Tan*40=20/x | | 3w*2-12+6= | | 2x+3=2x-2+4 | | 3x+4y+2=24 |

Equations solver categories